Relationship of Academic Stress and Emotional Eating with Obesity in Universitas Teuku Umar Nutrition Students - Dinda Rahma Yanti; Hanif Muchdatul Ayunda; Sufyan Anwar; Nasrianti Syam (Journal of Nutrition Science, 2025)
Final-year students often experience academic stress, impacting their concentration, motivation, and thesis completion. Additionally, emotional eating has known negative health consequences, with a significant link between depression and weight gain. This quantitative study aimed to explore the relationship between academic stress levels, emotional eating, and the incidence of obesity among 163 final-year nutrition students at Universitas Teuku Umar. Univariate and bivariate tests were conducted for analysis. The findings revealed a significant relationship between academic stress and obesity (p-value = 0.004 < 0.05), with a moderate correlation strength of 0.485. Similarly, a significant relationship was found between emotional eating and obesity (p-value = 0.000 < 0.05). Furthermore, a simultaneous significant relationship between academic stress, emotional eating, and obesity was identified (Chi-Square Asymp Sig = 0.004 < 0.005). The logistic regression model was deemed suitable (Sig value = 0.996 > 0.05), indicating its effectiveness in predicting the observed classifications. The independent variables explained 59.9% of the dependent variable, with other factors accounting for the remainder. In conclusion, academic stress and emotional eating significantly influence the incidence of obesity among final-year nutrition students at Universitas Teuku Umar.